Geographical Configuration and Accessibility of Tertiary Health Centres in Kasaragod - Sudha P; Dasharatha P. Angadi (International Journal of Scientific Research in Science and Technology, 2024)
The geographical configuration of the public and private health institutions is designed to ensure the quality healthcare services and available to all residents in their location, but it partially contributes to the overall wellbeing of the district’s population. The possibility to get healthcare services, including those related to illness, disorders, diagnosis, treatment and management of diseases and other situations that affect health is known as healthcare access. The possibility of obtaining health care exists and a population may "have access" to services if services are offered and there is a sufficient supply of them. Perceivable, operable, intelligible, and robust are the four fundamental criteria that guide accessibility. Accessibility of health care medical facilities in Kasaragod district depends on numerous aspects including location, transportation infrastructure, and available resources. In the field of medical geography, population health is greatly impacted by the accessibility of healthcare facilities. Everyone will be able to get equitable access to high-quality healthcare regardless of where they live if geographic obstacles are removed. The Endosulfan pesticide tragedy has affected Kerala's Kasaragod area, with some victims in the district. Individuals who obtain care from subpar medical facilities soon find that they have to go farther to receive it. The accessibility of health care facilities based on cost, travel time, and distance is a crucial factor that affects the general health and well-being of the community in this district, which is located in northern Kerala and has a population of over 1.4 million. The distance, cost, and time to healthcare facilities can all be determined using the Anova test technique. GIS tools such as Kernal Density, Nearest neighbourhood analysis are utilized to measure the spatial distribution of healthcare and population. The area with the fewest public healthcare services is the hilly Vellarikundu Taluk, which is located southeast of the Kasaragod district. Food quality, cleanliness, standard of living, cultural norms, and knowledge about illnesses, especially in the area of awareness campaigns, are all variables that affect the health of the population. In an emergency, it could be extremely challenging for residents of rural areas to get to medical facilities. Accessing healthcare facilities in rural and isolated places can provide a substantial problem, particularly for vulnerable groups including the elderly, pregnant women, and people with disabilities. Inadequate transportation infrastructure can lead to delays in reaching these centres, which can further affect the quality of service received. It is imperative that the government and local authorities allocate resources towards enhancing the accessibility of healthcare facilities in order to guarantee that all Kasaragod district inhabitants have prompt and efficient access to medical care.
Keywords: GIS; Accessibility; Infrastructure; Inhabitants; Kernal Density Estimation